Pengaruh Perubahan Temperatur Lingkungan terhadap Kinerja dan Efisiensi Turbin pada Pembangkit Listrik Tenaga Panas Bumi (PLTP) Unit 2 Lahendong - Prisilia Mariono; Rolles Nixon Palilingan; Armstrong F. Sompotan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
The Lahendong Geothermal Power Plant (PLTP) is the largest power plant in North Sulawesi. Turbine is one of the important components in a power plan, so performance and efficiency must be considered. Environmental temperatures that change on a daily basis can potentially affect turbine performance and efficiency. Therefore, it is necessary to analyze the turbine to determine whether the ambient temperature can affect the performance and efficiency of the turbine. The results of the study for 14 days at 10.00 and 22.00 showed differences in the value of turbine performance and efficiency. The turbine performance value is greater during the day than at night. Turbine efficiency is affected by the ambient temperature, when the ambient temperature increases there is a decrease in efficiency and when the temperature decreases there is an increase in turbine efficiency